3D Dynamic Simulation Of Reinforced Concrete Seals For 120 Psi Design Standard - R. Reddy Kallu (Society for Mining, Metallurgy & Exploration, 2009)
Prior to July 2007, the only accepted method by MSHA for evaluating the mine seal design and performance is the full-scale explosion tests conducted in the NIOSH?s Lake Lynn Experimental Mine (LLEM) for deeming a seal design suitable for use in U.S. coal mines. Since the new regulations came into effect use of these conventional full-scale explosion tests for evaluating mine seals for the new elevated design standards may not be practicable. Generation of such high explosion pressures in experimental mines is dangerous and may cause permanent damage to the testing facilities. Further, they require significant amount of time, labor and money. Considering these factors, there is a need to develop scientific methods for evaluation of new seal designs and for understanding the dynamic seal response. This paper tries to address the reinforced concrete (RC) seal design using the three dimensional finite element based explicit software ABAQUS. Full-scale explosion test data available from NIOSH?s LLEM on 20 psi reinforced concrete seal is used for validating the numerical models. Further in this paper, based on the results from the validation models, a reinforced concrete seal is designed for 120 psi design standard for typical entry dimensions.